The Function of Whatsapp Group as a Medium of Communication Government and People in Sinisir Village South Minahasa Regency - Meity Dina Himpong; Grace Jane Waleleng; Desie M.D. Warouw (Borong Newinera Publisher, 2023)
WhatsApp is one of the instant messaging applications used by 112 million people in Indonesia, including rural communities. Whatsapp is a popular technology that is also used as a communication medium for the government and rural communities. This study used qualitative research methods. For this reason, data collection was carried out using in-depth interviews, participant observation, document studies. The informants of this research are Government and Society. To answer the focus of this research, the theory used in this study is the Theory of Communication Media Function This research is also to develop Mass Media Courses and Development Communication Courses. The results showed that the function of WhatsApp Group as a medium of communication between the government and the community in Sinisir Village, South Minahasa Regency, is effective in implementing, realizing and improving services to the community, as well as a means of exchanging information between the government and the community. Efficient in time and cost, because in just one message can reach many people. Concrete as a medium or application that is seen, heard, read that governments and communities use to convey and receive messages. Able to motivate the community to support government programs with high enthusiasm.